Glass cloth, prepreg and printed wiring board

By adjusting the whiteness and weight reduction coefficient of the glass cloth, the problem of the reduced insulation reliability of the low-dielectric constant glass cloth during thermal cleaning is solved, and efficient insulation performance is achieved, and it is suitable for the production of precured materials and printed circuit boards.

JP2025039628AInactive Publication Date: 2025-03-21ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024232823
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the thermal cleaning process of low dielectric constant glass cloth, it is easy to cause the insulation reliability of prepregs to decrease, and it is difficult to perform sufficient heat treatment at high temperatures, affecting the performance of glass cloth.

Method used

By adjusting the whiteness and weight reduction coefficient of the glass line, the glass cloth has a predetermined weight reduction trend in the heat treatment of 380°C and the whiteness reaches 95 or above, thereby improving the insulation reliability of the glass cloth.

Benefits of technology

Excellent insulation reliability of precured materials of low dielectric constant glass cloth is achieved, and the overall performance of printed circuit boards is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039628000001
    Figure 2025039628000001
Patent Text Reader

Abstract

To provide a low dielectric glass cloth from which a prepreg excellent in insulation reliability can be produced, and a prepreg and a printed wiring board made of the low dielectric glass cloth.SOLUTION: A glass cloth including a glass yarn made of a plurality of glass filaments as warp and weft has a weight loss factor obtained as a product of a weight loss ratio derived from the glass component in heat treatment at 380°C for 2 hours and an average radius of the glass monofilament in the following equation (1) of 0.38 or more and 0.9 or less. The glass cloth has a whiteness degree of 95 or more. Weight loss factor=The weight loss ratio (%)×Average radius of the glass filament (μm) ... (1)SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a glass cloth, a prepreg, and a printed wiring board. [Background technology]

[0002] With the recent development of the information and communication society, data communication and / or signal processing have become large-volume and high-speed, and the dielectric constant of printed wiring boards used in electronic devices has been significantly reduced. For this reason, many low-dielectric glass cloths have been proposed as glass cloths for use in printed wiring boards.

[0003] For example, the low dielectric glass cloth disclosed in Patent Document 1 achieves a low dielectric constant by incorporating a large amount of B2O3 into the glass composition, as compared to the E-glass cloth that has been commonly used conventionally, while at the same time adjusting the amounts of other components such as SiO2. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-262632 A Summary of the Invention [Problem to be solved by the invention]

[0005] If the B2O3 content in the glass yarn is increased to reduce the dielectric constant of the glass cloth, the elastic modulus of the glass yarn decreases, making the glass yarn more susceptible to breakage during the manufacturing process. Therefore, as described in Patent Document 1, a coating process with a sizing agent is applied to the glass fiber bundle during spinning and warping, and a process called heat cleaning is applied after weaving to remove the sizing agent, which is an organic substance attached to the glass fiber bundle.

[0006] Examples of heat cleaning methods that have been conventionally and commonly used and are described in Patent Document 1 include a batch-type heat cleaning method at 350 to 500° C. and a heat cleaning method in which the glass cloth is continuously passed through a heating furnace at a high temperature of 550 to 700° C. However, it has been found that when such heat cleaning methods are applied to low dielectric glass cloth, prepregs with poor insulation reliability are mixed in when the glass cloth obtained by such methods is used.

[0007] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a low dielectric glass cloth capable of giving a prepreg having excellent insulation reliability, and a prepreg and a printed wiring board using the low dielectric glass cloth. [Means for solving the problem]

[0008] As a result of intensive research into solving the above-mentioned problems, the inventors discovered that the above-mentioned problems could be solved by setting the whiteness of a glass yarn having a predetermined weight loss tendency to a predetermined value, and thus completed the present invention.

[0009] That is, the present invention is as follows. [1] A glass cloth constructed by using glass yarns made of a plurality of glass filaments as warp yarns and weft yarns, In the following formula (1), a weight loss coefficient calculated as the product of the weight loss rate derived from the glass component in a heat treatment at 380° C. for 2 hours and the average radius of the glass monofilament is 0.38 or more and 0.9 or less, Weight reduction coefficient=weight reduction ratio (%)×average radius of the glass filaments (μm) (1) The whiteness is 95 or more. Glass cloth. [2] The glass cloth, The Si content is 40 to 60 mass% in terms of SiO2, The B content is 15 to 30 mass% calculated as B2O3, The glass cloth according to [1]. [3] The Fe content is 0.001 to 0.10 mass% in terms of Fe2O2. The glass cloth according to [1] or [2]. [4] Has a dielectric constant of 5.0 or less at a frequency of 1 GHz; The glass cloth according to any one of [1] to [3]. [5] [1] to [4], and and a matrix resin impregnated in the glass cloth. Prepreg. [6] The glass cloth according to any one of [1] to [4] is provided. Printed wiring board. Effect of the Invention

[0010] According to the present invention, it is possible to provide a low dielectric glass cloth capable of giving a prepreg having excellent insulation reliability, and a prepreg and a printed wiring board using the low dielectric glass cloth. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Below, an embodiment of the present invention (hereinafter referred to as "the present embodiment") will be described in detail, but the present invention is not limited to this embodiment, and various modifications are possible without departing from the gist of the present invention.

[0012] [Glass cloth] The glass cloth of the present embodiment is a glass cloth constituted of glass yarns consisting of a plurality of glass filaments as warp and weft yarns, and has a weight reduction coefficient calculated as the product of the weight reduction rate derived from the glass component in a heat treatment at 380°C for 2 hours and the average radius of the glass filaments in the following formula (1) of 0.38 to 0.90, and a whiteness of 95 or more. Weight reduction coefficient = weight reduction ratio (%) × average radius of glass filaments (μm) (1)

[0013] It has been found that when a low dielectric constant glass cloth obtained by conventional heat cleaning is used, a printed wiring board with poor insulation reliability is obtained. The greater the low dielectric effect of the glass cloth, the poorer the insulation reliability tends to be. The reason for this is unclear, but one of the causes is thought to be that the sizing agent, which should be removed by heat in heat cleaning, produces a flame-retardant reaction product, which is not removed and remains on the glass cloth. That is, it is presumed that the components constituting the low dielectric glass cloth have some catalytic action, which causes the sizing agent to denature into a flame-retardant component, making it difficult to remove. This situation was not evident in conventional E-glass cloth and the like. It is thought that the decrease in insulation reliability when the residual amount is about the same tends to be more significant in low dielectric glass cloth compared to E-glass cloth and the like. Furthermore, there is a limitation in that it is difficult to perform a sufficient high-temperature treatment in heat cleaning because the components constituting the glass tend to volatilize at high temperatures. Therefore, in this embodiment, it is specified that the glass cloth has a predetermined weight reduction tendency.

[0014] Furthermore, in this embodiment, the whiteness of the glass cloth is also adjusted. The glass cloth of this embodiment is obtained through a desizing process in which the sizing agent attached to the glass yarns of the glass cloth is removed, as described below. In this desizing process, the glass cloth is heat-treated to remove the sizing agent attached to the glass yarns, but in glass cloth that is difficult to treat at high temperatures as described above, the sizing agent may not be sufficiently removed and may remain on the glass cloth. When this remaining sizing agent was examined, it was found that there was little remaining sizing agent on the surface of the glass cloth, and even if there was any remaining sizing agent, it was mostly whitish gray-like, which is smooth and easy to physically remove. On the other hand, it was found that there was a lot of dark viscous matter that was difficult to remove in the parts where the glass yarns were intricate, such as the weave (the intersection of the warp and weft threads). This is presumably because the sizing agent was difficult to remove in the parts where the glass yarns were intricate, and a viscous matter (a flame-retardant reaction product) was generated as the heat treatment progressed. Further examination revealed that such viscous matter is relatively hygroscopic, which improves the hygroscopicity of the glass cloth and reduces the insulation reliability. In particular, it has been found that in those with a certain tendency for weight loss, the parts that evaporate from the glass yarn and are lost are prone to absorbing moisture, and if this viscous matter adheres to these parts, it leads to a further decrease in insulation reliability.

[0015] In this embodiment, whiteness is used as an index showing the amount of viscous matter, and it is specified that the whiteness of a glass cloth that satisfies a predetermined weight loss tendency is a predetermined value or more. This makes it possible to provide a glass cloth that can provide a printed wiring board with excellent insulation reliability. The configuration of this embodiment will be described in more detail below.

[0016] (Weight reduction coefficient) The weight loss coefficient (hereinafter, also simply referred to as "weight loss coefficient") calculated as the product of the weight loss rate derived from the glass component and the average radius of the glass filaments when the glass cloth is heat-treated at 380°C for 2 hours is 0.38 or more and 0.90 or less, preferably 0.42 or more and 0.85 or less, and more preferably 0.46 or more and 0.80 or less.

[0017] "Weight loss ratio derived from glass components" means that the weight loss ratio in the case of heat treatment at 380°C for 2 hours is due to the disappearance of glass components due to volatilization during heat treatment. As described later, in the present embodiment, when a surface treatment agent such as a silane coupling agent is attached to the glass cloth or when a large amount of organic impurities is attached, the weight loss ratio is calculated after removing the surface treatment agent such as a silane coupling agent or the organic impurity attached components that are physically adsorbed with a good solvent such as alcohol or acetone. Therefore, the weight loss ratio of the glass cloth after heat treatment after removing the attached components that are decomposed by heat at 380°C is the weight loss ratio derived from the glass components.

[0018] It was also confirmed that the weight reduction rate depends on the filament diameter of the glass yarn. The weight reduction rate varies depending on the glass filament diameter, and the smaller the filament diameter, the greater the weight reduction amount. On the other hand, the product of the weight reduction rate and the filament radius is an almost constant value regardless of the filament diameter. Therefore, in this embodiment, the weight reduction coefficient is standardized by the filament diameter.

[0019] By having a weight reduction coefficient of 0.38 or more, the glass is easily affected by the hygroscopic viscous matter if left as is, and the insulation reliability of the obtained prepreg is likely to be reduced. In other words, it is considered that the reduction in insulation reliability when the remaining amount of the viscous matter is the same tends to be more significant in the low dielectric glass cloth than in the E-glass cloth, which has a small weight reduction coefficient. In contrast, in this embodiment, the whiteness is used as an indicator of the remaining amount of the viscous matter, and the weight reduction tendency and the whiteness are each defined within a specific range and combined to improve the insulation reliability of the obtained printed wiring board. In addition, by having a weight reduction coefficient of 0.90 or less, the hygroscopicity of the glass itself does not become too large, and a significant reduction in insulation reliability can be suppressed.

[0020] The weight loss ratio can be measured by the following procedure. First, the glass cloth is placed in a dryer at 105°C ± 5°C and dried for 60 minutes, then the glass cloth is transferred to a desiccator and allowed to cool to room temperature. After cooling, the weight of the glass cloth is measured to the nearest 0.1 mg (glass cloth weight a). Next, the glass cloth is heated at 380°C for 2 hours, then the glass cloth is transferred to a desiccator and allowed to cool to room temperature. After cooling, the weight of the glass cloth is measured to the nearest 0.1 mg (glass cloth weight b after heat treatment). The weight lost due to the heat treatment is then determined, and the weight loss ratio (%) is calculated using the following formula (2). Weight reduction rate (%) = (ab) / a×100 ···(2)

[0021] The weight loss rate obtained as described above is preferably 0.05 to 0.7%, more preferably 0.1 to 0.5%, and even more preferably 0.12 to 0.4%. If the weight loss rate is 0.05% or more, the insulation reliability is likely to decrease if left as is. However, in this embodiment, the decrease in insulation reliability can be suppressed by adjusting the whiteness described below, and a glass cloth having a lower dielectric constant can be obtained from the composition of the glass cloth. Furthermore, if the weight loss rate is 0.7% or less, a significant decrease in insulation reliability can be suppressed.

[0022] Next, the average diameter of the glass filaments of the glass yarn constituting the glass cloth is measured in accordance with JIS R3420, and the average filament diameter is calculated as half of the filament diameter. In this embodiment, when simply referring to glass filaments, it means glass monofilaments. The average radius of the glass filaments used in calculating the weight reduction coefficient is the average radius before the heat treatment. The average radius of the glass filaments thus calculated is preferably 1.25 to 4.5 μm, more preferably 1.5 to 3.75 μm, and even more preferably 1.75 to 2.7 μm.

[0023] The glass cloth used in the above-mentioned method for measuring the weight loss rate can be appropriately pretreated. For example, the glass cloth unwound from the intermediate roll after desizing (heat cleaning) has no attached matter on the glass filaments, and can be used as is in the above-mentioned method for measuring the weight loss rate.

[0024] On the other hand, when determining the weight reduction ratio for glass cloth to which a surface treatment agent such as a silane coupling agent has been applied, the physically adsorbed surface treatment agent such as the silane coupling agent can be washed away in advance with a good solvent such as alcohol or acetone, and then the weight reduction coefficient can be determined by the above method.

[0025] The term "physically adsorbed silane coupling agent" refers to a silane coupling agent that is attached to the glass filament, but is not a silane coupling agent that is bonded to the glass filament by a chemical bond. In contrast, a silane coupling agent that is bonded to the glass filament by a chemical bond is called a "chemically adsorbed silane coupling agent."

[0026] In addition, when the glass cloth contains organic impurities (such as a starch-based sizing agent applied during the glass yarn manufacturing process, or combustion residues in the heat cleaning process of the sizing agent), the weight reduction coefficient can be determined by the above method after removing the organic impurities adhering to the glass cloth in advance by a cleaning removal operation using alcohol, acetone, or the like.

[0027] The above-mentioned washing is to remove physically adsorbed silane coupling agent and organic impurities, and is not to remove chemically adsorbed silane coupling agent.However, even if heated at 380°C for 2 hours, chemically adsorbed silane coupling agent does not decompose, and even if a part of it decomposes, it does not exceed the error range, so in the measurement of weight loss rate in this embodiment, it is not necessary to remove chemically adsorbed silane coupling agent by pretreatment.

[0028] From the viewpoint of simplifying the decision as to whether or not to perform pretreatment, the glass cloth may be uniformly washed in advance with a good solvent such as alcohols, acetone, etc. for the measurement of the weight loss ratio. This allows the weight loss ratio to be measured under the same conditions, even if the glass cloth is pulled out from the intermediate roll after desizing treatment (heat cleaning) or has physically adsorbed silane coupling agent or organic impurities attached thereto.

[0029] As another method, when determining the weight loss coefficient, the amount of the surface treatment agent and organic impurities before and after heating are quantified, and the weight loss caused by the surface treatment agent is subtracted from the weight loss obtained to determine the weight loss coefficient derived from the glass component. As a method for determining the weight loss caused by the surface treatment agent, a known method such as the method for quantifying the amount of a silane coupling agent described in Japanese Patent No. 6472082 may be used.

[0030] The weight loss coefficient can be adjusted by increasing or decreasing a relatively volatile component in the composition of the glass cloth, such as the B content, and from a similar viewpoint, it can also be adjusted by increasing or decreasing other components.

[0031] In addition, the weight reduction coefficient can also be adjusted by increasing or decreasing the frequency with which the glass surface is exposed to a high-temperature atmosphere, by adjusting the spatial filling rate of glass in the glass cloth (weaving density or thickness), adjusting the degree of unraveling of the monofilaments constituting the glass yarn bundle by fiber-opening processing or the like, adjusting the monofilament diameter of the glass yarn used, and so on. That is, the weight reduction coefficient is not determined only by the composition of the glass cloth.

[0032] (whiteness) The whiteness is 95 or more, preferably 95.5 or more, more preferably 96 or more, and even more preferably 97 or more. The upper limit of the whiteness is not particularly limited, but the upper limit is about 99.5, which is a value that reflects the color tone of the glass itself. By having a whiteness of 95 or more, the insulation reliability is further improved. The whiteness can be measured in accordance with JIS2000 L1916, a method for measuring the color of textile products.

[0033] In addition, the whiteness can be improved by reducing the amount of sizing agent (also called paste), increasing the heat treatment temperature, changing the composition of the sizing agent, or changing the composition of the glass cloth.

[0034] (composition) The composition of the glass cloth of this embodiment will be described below. The composition of the glass cloth is synonymous with the composition of the glass yarn constituting the glass cloth. In the composition of the glass cloth of this embodiment, the Fe content is preferably 0.001% by mass or more and 0.10% by mass or less, more preferably 0.001% by mass or more and 0.08% by mass or less, and even more preferably 0.01% by mass or more and 0.05% by mass or less, calculated as Fe2O3. By making the Fe content 0.10% by mass or less, the insulation reliability of the obtained prepreg can be further improved. This is presumed to be because the Fe content, which is considered to have a relatively general catalytic activity, is reduced to a specific range or less, thereby suppressing the sizing agent from being modified into a flame retardant component. The lower limit of the Fe content is not particularly limited, but is 0.001% by mass or more. The Fe content can be adjusted according to the amount of raw material used to prepare the glass filaments, purification removal from the raw materials by a magnet filter or the like, additional addition, etc.

[0035] The Si content of the glass cloth is preferably 40 to 60 mass%, more preferably 45 to 55 mass%, further preferably 47 to 53 mass%, and 48 to 52 mass% in terms of SiO2. Si is a component that forms the skeletal structure of the glass yarn, and when the Si content is 40 mass% or more, the strength of the glass yarn is improved, and the breakage of the glass cloth tends to be suppressed more in the manufacturing process of the glass cloth and in the post-process such as the manufacturing of a prepreg using the glass cloth. In addition, when the Si content is 40 mass% or more, the dielectric constant of the glass cloth tends to be lowered more. On the other hand, when the Si content is 60 mass% or less, the viscosity at the time of melting is lowered more in the manufacturing process of the glass filament, and glass fibers with a more homogeneous glass composition are obtained, and as a result, the glass cloth is less likely to break. The Si content can be adjusted according to the amount of raw material used to manufacture the glass filament.

[0036] The B content of the glass cloth is preferably 15 to 30 mass%, more preferably 17 to 28 mass%, further preferably 20 to 27 mass%, further more preferably 21 to 25 mass%, and further more preferably 21.5 to 24 mass%, calculated as B2O3. When the B content is 15 mass% or more, the dielectric constant tends to be lower. When the B content is 30 mass% or less, the moisture absorption resistance is improved, and the insulation reliability tends to be improved. The B content can be adjusted according to the amount of raw material used in the production of the glass filaments. When the B content may vary during the production of the glass filaments, the amount of the raw material can be adjusted in advance in anticipation of this.

[0037] The F content of the glass cloth is preferably 0.001 to 0.1% by mass, more preferably 0.001 to 0.07% by mass, and further preferably 0.001 to 0.05% by mass. Here, the F content is a value obtained by converting it to F2. When the F content is within the above range, the breakage of the glass cloth tends to be more suppressed. The reason why the breakage of the glass cloth is suppressed by adjusting the F content is not limited, but is thought to be as follows. F reduces the viscosity of molten glass in the glass manufacturing process. Therefore, when the F content is within a predetermined range, metal components such as Fe can be uniformly dispersed without localization when they are incorporated into the glass structure, and uniform glass can be formed. When Fe is uniformly dispersed, it is considered that the effect of suppressing the above-mentioned sizing agent from being modified into a flame-retardant component can be more effectively expressed. The F content can be adjusted according to the amount of raw material used to prepare the glass filaments.

[0038] The glass filaments may have other compositions in addition to those described above, including, but not limited to, Al, Ca, Mg, P, Na, K, Ti, and Zn.

[0039] The Al content of the glass cloth is preferably 10 to 20 mass%, more preferably 12 to 18 mass%, and further preferably 14 to 17 mass%, calculated as Al2O3. When the Al content is within the above range, the electrical properties and strength tend to be further improved. The Al content can be adjusted according to the amount of raw material used to prepare the glass filaments.

[0040] The Ca content of the glass cloth is preferably 1.0 to 6.0 mass%, preferably 2.0 to 5.0 mass%, and more preferably 2.5 to 4.0 mass%, calculated as CaO. When the Ca content is 1.0 mass% or more, the viscosity at the time of melting is further reduced in the manufacturing process of the glass filaments, and glass fibers having a more homogeneous glass composition tend to be obtained. Also, when the Ca content is 6.0 mass% or less, the dielectric constant tends to be further improved. The Ca content can be adjusted according to the amount of raw material used in manufacturing the glass filaments.

[0041] The Mg content of the glass cloth is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, still more preferably 0.01 to 1.0% by mass or less, even more preferably 0.05 to 0.5% by mass or less, and even more preferably 0.05 to 0.3% by mass or less, calculated as MgO. When the Mg content is 5.0% by mass or less, the glass cloth is less likely to break when passing through a squeeze roll or nip roll in a wet state in a fiber opening process or a surface treatment process during glass cloth production. In addition, phase separation during glass filament production is suppressed, and the moisture absorption resistance of the obtained glass filament is further improved. As a result, the obtained printed wiring board is less susceptible to the influence of a high humidity environment, and the environmental dependency of the dielectric constant can be reduced. The Mg content can be adjusted according to the amount of raw material used for producing the glass filament.

[0042] The P content of the glass cloth is preferably 1.0 to 7.0 mass%, more preferably 2.0 to 6.0 mass%, further preferably 3.0 to 6.0 mass%, and even more preferably 3.0 to 5.5 mass%, calculated as P2O5. When the P content is 1.0 mass% or more, the dielectric constant tends to be lowered. When the P content is 7.0 mass% or less, the glass cloth tends to be less likely to break when passing through a squeeze roll or nip roll in a wet state in a fiber opening process or a surface treatment process during glass cloth production. In addition, phase separation during glass filament production is suppressed, and the moisture absorption resistance of the obtained glass filament is further improved. As a result, the obtained printed wiring board is less susceptible to the effect of a high humidity environment, and the environmental dependency of the dielectric constant can be reduced. The P content can be adjusted according to the amount of raw material used in glass filament production.

[0043] The above contents can be measured by ICP atomic emission spectrometry. Specifically, the Si content and B content can be obtained by decomposing a weighed glass cloth sample with sodium hydroxide under pressure, dissolving it with dilute nitric acid, and filtering it. The insoluble matter is then melted with sodium carbonate, combined with the filtrate to a constant volume, and the obtained sample is measured by ICP atomic emission spectrometry.

[0044] The Fe content, Al content, Ca content, Ma content, and P content can be obtained by decomposing a weighed glass cloth sample by heating with perchloric acid, nitric acid, hydrochloric acid, and hydrogen fluoride, dissolving by heating with dilute aqua regia, and filtering the sample. The filtrate is made to a constant volume. The insoluble portion is then decomposed by heating with sulfuric acid, nitric acid, hydrochloric acid, and hydrogen fluoride to a constant solution, and the obtained sample is measured by ICP atomic emission spectrometry. The ICP atomic emission spectrometry can be performed using a PS3520VDD II manufactured by Hitachi High-Tech Science Corporation.

[0045] The F content was measured by burning a weighed glass cloth sample in a tubular electric furnace, and then absorbing the generated gas into an absorbing solution. The solution was analyzed by ion chromatography to determine the amount of fluoride ions (F -) can be measured to determine the amount of chlorine contained in the sample. The combustion device can be an automatic sample combustion device (AQF-2100S) manufactured by Mitsubishi Chemical Analytech, and the measurement device can be an ion chromatograph ICS-1500 manufactured by Thermo Fisher Scientific.

[0046] The elastic modulus of the glass cloth is preferably 50 to 70 GPa, more preferably 50 to 63 GPa, further preferably 53 to 63 GPa, and particularly preferably 53 to 60 GPa. The lower the elastic modulus of the glass cloth, the more likely it is to break. Therefore, when the elastic modulus is 50 GPa or more, in the glass cloth manufacturing process such as the opening process and the surface treatment process, the glass cloth tends to be less likely to break when it passes through a squeeze roll or a nip roll in a wet state. Also, in the post-process such as the manufacture of prepreg, when the glass cloth is passed through a slit for the purpose of controlling the amount of resin impregnated into the glass cloth, the glass cloth tends to be less likely to break. Also, when the elastic modulus of the glass yarn is 70 GPa or less, the dielectric constant tends to be relatively lower. The elastic modulus can be measured by the method described in the examples. Also, the elastic modulus can be adjusted by the composition of the glass yarn.

[0047] The dielectric constant of the glass cloth of this embodiment is preferably 5.0 or less, more preferably 4.7 or less, further preferably 4.5 or less, and particularly preferably 4.0 or less, at a frequency of 1 GHz. In this embodiment, the dielectric constant refers to the dielectric constant at a frequency of 1 GHz, unless otherwise specified.

[0048] (composition) Glass yarn is obtained by bundling a plurality of glass filaments and twisting them as necessary, and glass cloth is obtained by weaving the above glass yarns as warp and weft. Glass yarns are classified into multifilament and glass filaments are classified into monofilament.

[0049] The average diameter of the glass filaments constituting the warp and weft is preferably 2.5 to 9 μm, more preferably 3.0 to 7.5 μm, and even more preferably 3.5 to 5.4 μm. When the average diameter of the glass filaments is within the above range, the processability of the obtained substrate tends to be improved when processed by a mechanical drill, a carbon dioxide gas laser, or a UV-YAG laser. Therefore, a thin and highly dense printed wiring board can be realized. In particular, when the average diameter is 5.4 μm or less, the weight loss amount for the same heating time increases, so that the hygroscopicity of the glass cloth itself tends to increase. In addition, the surface area per unit volume of the glass filaments increases, so that the amount of adhesion of hygroscopic viscous matter derived from the sizing agent increases, and the hygroscopicity of the glass cloth is promoted, so that the effect of improving the insulation reliability of this embodiment becomes more important. In addition, when the average diameter is 2.5 μm or more, breakage tends to be less likely to occur when the glass cloth passes through a squeeze roll, a nip roll, or the like in a wet state in the glass cloth manufacturing process such as the opening process and the surface treatment process. Furthermore, in post-processes such as the production of prepregs, breakage tends to be less likely to occur when the glass cloth is passed through a slit for the purpose of controlling the amount of resin impregnated into the glass cloth.

[0050] The weft density of the warp and weft threads constituting the glass cloth is preferably 30 to 120 threads / 25 mm, more preferably 40 to 110 threads / 25 mm, and further preferably 50 to 100 threads / 25 mm.

[0051] The thickness of the glass cloth is preferably 8 to 100 μm, more preferably 10 to 70 μm, and further preferably 12 to 50 μm. When the thickness of the glass cloth is within the above range, a thin glass cloth with relatively high strength tends to be obtained. The weight reduction coefficient depends on the area of ​​the glass cloth and on the diameter of the filaments constituting the glass cloth, and is therefore unlikely to depend on the thickness. This tendency is maintained at least within the above thickness range.

[0052] The fabric weight (weight) of the glass cloth is preferably 8 to 250 g / m 2 and more preferably 8 to 100 g / m 2 and more preferably 8 to 50 g / m 2 and particularly preferably 8 to 35 g / m 2 It is.

[0053] The weave structure of the glass cloth is not particularly limited, but examples thereof include plain weave, sash weave, satin weave, twill weave, etc. Among these, the plain weave structure is more preferable.

[0054] (Surface treatment) The glass cloth may be surface-treated with a surface treatment agent. The surface treatment agent is not particularly limited, but may be, for example, a silane coupling agent, and may be used in combination with water, an organic solvent, an acid, a dye, a pigment, a surfactant, or the like, as necessary.

[0055] The silane coupling agent is not particularly limited, but examples thereof include compounds represented by formula (1). X(R) 3-n SiY n (1) (In formula (1), X is an organic functional group having at least one of an amino group and an unsaturated double bond group, each Y is independently an alkoxy group, n is an integer of 1 to 3, and each R is independently a group selected from the group consisting of a methyl group, an ethyl group, and a phenyl group.)

[0056] X is preferably an organic functional group having at least three or more of amino groups and unsaturated double bond groups, and more preferably an organic functional group having at least four or more of amino groups and unsaturated double bond groups.

[0057] The alkoxy group may be in any form, but from the viewpoint of stabilizing the treatment of the glass cloth, an alkoxy group having 5 or less carbon atoms is preferred.

[0058] Specific examples of the silane coupling agent include N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane and its hydrochloride, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropylmethyldimethoxysilane and its hydrochloride, N-β-(N-di(vinylbenzyl)aminoethyl)-γ-aminopropyltrimethoxysilane and its hydrochloride, N-β-(N-di(vinylbenzyl)aminoethyl)-N-γ-(N-vinylbenzyl)-γ-aminopropyltrimethoxysilane and its hydrochloride, N-β Examples of known simple substances include -(N-benzylaminoethyl)-γ-aminopropyltrimethoxysilane and its hydrochloride, N-β-(N-benzylaminoethyl)-γ-aminopropyltriisoethoxysilane and its hydrochloride, γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropyltriethoxysilane, aminopropyltrimethoxysilane, vinyltrimethoxysilane, methacryloxypropyltrimethoxysilane, acryloxypropyltrimethoxysilane, and the like, or mixtures thereof.

[0059] The molecular weight of the silane coupling agent is preferably 100 to 600, more preferably 150 to 500, and further preferably 200 to 450. Among these, it is preferable to use two or more silane coupling agents having different molecular weights. By treating the surface of the glass yarn with two or more silane coupling agents having different molecular weights, the density of the surface treatment agent on the surface of the glass cloth increases, and the reactivity with the matrix resin tends to be further improved.

[0060] [Method of manufacturing glass cloth] The method for producing the glass cloth of the present embodiment is not particularly limited, but may include, for example, a method having a weaving step of weaving glass yarns to obtain a glass cloth, a spreading step of spreading the glass yarns of the glass cloth, and a desizing step of removing the sizing agent attached to the glass yarns of the glass cloth. If necessary, the method may also include a surface treatment step using a silane coupling agent.

[0061] The weaving method is not particularly limited as long as it is a method of folding the warp and weft threads to form a predetermined weave structure. The opening method is not particularly limited, but examples thereof include opening processing using spray water (high pressure water opening), a vibro washer, ultrasonic water, a mangle, etc.

[0062] Furthermore, the desizing method is not particularly limited, but for example, a method of removing the sizing agent by heating can be mentioned. The sizing agent is used for the purpose of protecting the glass yarn from thread breakage during the weaving process and the like. Such a sizing agent is not particularly limited, but for example, a starch-based binder and a polyvinyl alcohol-based binder can be mentioned. The temperature when removing the sizing agent by heating is preferably 300 to 500°C, more preferably 330 to 450°C, and even more preferably 350 to 430°C, from the viewpoint of sufficiently removing the sizing agent while maintaining the breaking strength.

[0063] Also, examples of the surface treatment method include a method of contacting a surface treatment agent containing a silane coupling agent with a glass cloth and drying it. Examples of the contact of the surface treatment agent with the glass cloth include a method of immersing the glass cloth in the surface treatment agent, and a method of applying the surface treatment agent to the glass cloth using a roll coater, a die coater, a gravure coater, or the like. There are no particular limitations on the method of drying the surface treatment agent, and examples of the method include hot air drying and drying methods using electromagnetic waves.

[0064] [Prepreg] The prepreg of the present embodiment includes the above-mentioned glass cloth and a matrix resin composition impregnated into the glass cloth. The prepreg including the above-mentioned glass cloth has improved insulation reliability and high yield of the final product. In addition, it is possible to provide a printed wiring board having excellent dielectric properties and excellent moisture absorption resistance, and therefore has little variation in dielectric constant due to the influence of the usage environment, particularly in a high humidity environment.

[0065] The prepreg of the present embodiment can be produced by a conventional method, for example, by impregnating the glass cloth of the present embodiment with a varnish prepared by diluting a matrix resin such as an epoxy resin with an organic solvent, volatilizing the organic solvent in a drying furnace, and curing the thermosetting resin to a B-stage state (semi-cured state).

[0066] Examples of the matrix resin composition include, in addition to the above-mentioned epoxy resins, thermosetting resins such as bismaleimide resins, cyanate ester resins, unsaturated polyester resins, polyimide resins, BT resins, and functionalized polyphenylene ether resins; thermoplastic resins such as polyphenylene ether resins, polyetherimide resins, liquid crystal polymers (LCPs) of wholly aromatic polyesters, polybutadiene, and fluororesins; and mixed resins thereof. From the viewpoint of improving dielectric properties, heat resistance, solvent resistance, and press moldability, the matrix resin composition may be a resin obtained by modifying a thermoplastic resin with a thermosetting resin.

[0067] The matrix resin composition may also contain inorganic fillers such as silica and aluminum hydroxide; flame retardants such as bromine-based, phosphorus-based, and metal hydroxides; other silane coupling agents; heat stabilizers; antistatic agents; ultraviolet absorbers; pigments; colorants; lubricants, etc.

[0068] [Printed Wiring Board] The printed wiring board of this embodiment includes the above-mentioned glass cloth. The printed wiring board of this embodiment has improved insulation reliability and high yield of the final product. In addition, since the printed wiring board has excellent dielectric properties and excellent moisture absorption resistance, it has the effect of being less susceptible to the influence of the usage environment, particularly in a high humidity environment, and has a small change in dielectric constant. EXAMPLES

[0069] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.

[0070] [Physical properties of glass cloth] The physical properties of the glass cloth, specifically, the thickness of the glass cloth, the diameter of the filaments constituting the warp and weft, the number of filaments, and the weaving density (weaving density) of the warp and weft were measured in accordance with JIS R3420.

[0071] [Weight reduction coefficient] The weight loss coefficient was measured by the following procedure. First, the glass cloth pulled out from the intermediate roll was placed in a dryer at 105°C ± 5°C and dried for 60 minutes, then the glass cloth was transferred to a desiccator and allowed to cool to room temperature. After cooling, the weight of the glass cloth was measured to the nearest 0.1 mg (weight of glass cloth a). Next, the glass cloth was heated at 380°C for 2 hours, then the glass cloth was transferred to a desiccator and allowed to cool to room temperature. After cooling, the weight of the glass cloth was measured to the nearest 0.1 mg (weight of glass cloth after heat treatment b). Then, the weight reduction due to the heat treatment was determined, and the weight reduction ratio (%) was calculated using the following formula (2). Weight reduction rate (%) = (ab) / a×100 ···(2)

[0072] Next, the diameter of the monofilament was measured according to JIS R3420, Method B, and half of that value was defined as the radius of the monofilament. Although JIS R3420, Method B, requires that the diameters of 25 randomly selected filament cross sections be measured, the diameters of all the monofilaments constituting the glass yarn (multifilament) were measured, and the filament diameter was calculated as the average value. The weight loss coefficient was calculated from the weight loss rate (%) and the average radius (μm) of the glass filaments according to the following formula (1). Weight reduction coefficient = weight reduction ratio (%) × average radius of glass filaments (μm) (1)

[0073] [Glass yarn composition] The composition of the glass cloth was measured by ICP atomic emission spectrometry. Specifically, the Si content and B content were measured by pressure-decomposing a weighed glass cloth sample with sodium hydroxide, dissolving it in dilute nitric acid, and filtering it. The insoluble matter was dissolved in sodium carbonate, combined with the filtrate, and the volume was determined. The obtained sample was measured by ICP atomic emission spectrometry.

[0074] The Fe, Al, Ca, Ma, and P contents were measured by decomposing the weighed glass cloth sample with perchloric acid, nitric acid, hydrochloric acid, and hydrogen fluoride, then dissolving it by heating with dilute aqua regia and filtering it. The filtrate was made to a constant volume. The insoluble matter was decomposed with sulfuric acid, nitric acid, hydrochloric acid, and hydrogen fluoride, and dissolved to a constant volume. The obtained sample was measured by ICP atomic emission spectrometry. The ICP atomic emission spectrometry was performed using a PS3520VDD II manufactured by Hitachi High-Tech Science Corporation.

[0075] Furthermore, the F content was measured by burning a weighed glass cloth sample in a tubular electric furnace, and then absorbing the generated gas into an absorbing solution. The solution was analyzed by ion chromatography to determine the amount of fluoride ions (F - The content in the sample was calculated by measuring the amount of benzene in the sample. The combustion device used was an automatic sample combustion device (AQF-2100S) manufactured by Mitsubishi Chemical Analytech, and the measurement device was an ion chromatograph ICS-1500 manufactured by Thermo Fisher Scientific.

[0076] [Measurement of whiteness] The whiteness was measured using a spectrophotometer (CM-2600d, manufactured by Konica Minolta) in accordance with the JIS2000 L1916 method for measuring the color of textile products. The whiteness was measured by folding eight sheets of glass cloth, and the average value of five measurements was calculated.

[0077] [Evaluation of insulation reliability] <How to prepare the substrate> The glass cloth obtained in each of the Examples and Comparative Examples was impregnated with an epoxy resin varnish (a mixture of 40 parts by mass of low-brominated bisphenol A type epoxy resin (manufactured by Mitsubishi Chemical Corporation), 10 parts by mass of O-cresol type novolac epoxy resin (manufactured by Mitsubishi Chemical Corporation), 50 parts by mass of dimethylformamide, 1 part by mass of dicyandiamide, and 0.1 parts by mass of 2-ethyl-4-methylimidazole), and dried at 160°C for 2 minutes to obtain prepregs having a resin content of 78% by mass in Examples 1 to 3, Comparative Examples 1 to 6, and Reference Example 1, a resin content of 73% by mass in Example 4, and a resin content of 58% by mass in Example 5. A predetermined number of these prepregs were stacked, and copper foil having a thickness of 12 μm was further stacked on top and bottom, and the resulting mixture was heated at 175°C and 40 kg / cm. 2 The resulting substrate was heated and pressed at 400° C. for 60 minutes to obtain a substrate with a thickness of approximately 0.4 mm. A wiring pattern with through holes spaced 0.15 mm apart was formed on the copper foil on both sides of the resulting substrate to obtain a test substrate for evaluating insulation reliability.

[0078] <Method of evaluating the insulation reliability of substrate> A voltage of 10 V was applied to the obtained test board in an atmosphere of a temperature of 120° C. and a humidity of 85% RH, and the change in resistance value was measured. A resistance of less than 1 MQ within 500 hours after the start of the test was counted as an insulation failure.

[0079] 100 test boards were prepared, and 30 prepregs were randomly selected from them to measure the insulation reliability. Based on the measurement results, the insulation reliability was evaluated according to the following evaluation criteria. A: None of the test boards exhibited insulation failure. B: One prepreg showed insulation failure. C: There were two prepregs that showed insulation failure. D: Three or more prepregs showed insulation defects.

[0080] [Examples 1 to 3] Glass yarns (average filament diameter: 4.0 μm, number of filaments: 50) having the composition shown in Table 1 were woven using an air jet loom to obtain a glass cloth with a warp and weft density of 95 / 25 mm and a thickness of 14 μm. Next, a heat cleaning treatment was performed by heating at 400° C. for 24 hours, and a fiber opening process was performed using a high-pressure water spray to obtain a glass cloth intermediate with a width of 1280 mm and a length of 2000 m. Next, a surface treatment was performed using a silane coupling agent to produce a glass cloth.

[0081] Example 4 A roll of glass cloth was obtained in the same manner as in Example 2, except that a low dielectric glass yarn consisting of 100 filaments with an average filament diameter of 5.0 μm was woven to produce a glass cloth with a warp thread pick density of 65 and a weft thread pick density of 67 / 25 mm. The thickness of the obtained glass cloth was 30 μm, and the composition was as shown in Table 1.

[0082] Example 5 A roll of glass cloth was obtained in the same manner as in Example 2, except that a low dielectric glass yarn consisting of 200 filaments with an average filament diameter of 7.0 μm was woven and the glass cloth was produced with a warp and weft pick density of 52.5 yarns / 25 mm. The thickness of the obtained glass cloth was 92 μm, and the composition was as shown in Table 1.

[0083] Example 6 A roll of glass cloth was obtained in the same manner as in Comparative Example 5, except that after the heat cleaning, the glass cloth was washed with water in an attempt to wash and remove the sizing agent combustion residue remaining after the heat cleaning. The composition of the obtained glass cloth was as shown in Table 1.

[0084] [Comparative Examples 1, 3, and 6] Except for the different composition of the glass yarn, a roll of glass cloth was obtained in the same manner as in Example 1. The composition of the obtained glass cloth was as shown in Table 1.

[0085] Comparative Example 2 Except for changing the heat cleaning treatment time to 48 hours, a roll of glass cloth was obtained in the same manner as in Comparative Example 1. The composition of the obtained glass cloth was as shown in Table 1.

[0086] Comparative Example 4 Except for changing the heat cleaning treatment time to 48 hours, a glass cloth roll was obtained in the same manner as in Comparative Example 3. The composition of the obtained glass cloth was as shown in Table 1.

[0087] Comparative Example 5 A roll of glass cloth was obtained in the same manner as in Comparative Example 3, except that the glass cloth was washed with water before the heat cleaning treatment to try to reduce the amount of sizing agent before the heat cleaning treatment. The composition of the obtained glass cloth was as shown in Table 1.

[0088] [Reference example 1] Except for changing the composition of the glass yarn to a so-called E glass composition, a roll of glass cloth was obtained in the same manner as in Example 1. The composition of the obtained glass cloth was as shown in Table 1.

[0089] [Table 1]

[0090] When the glass cloth of the Examples was used, a substrate with high insulation reliability was obtained, and the incidence of substrates with poor insulation reliability was low. The glass cloth of Reference Example 1 had poor whiteness, but the incidence of substrates with poor insulation reliability was low, suggesting that the problem of reduced insulation reliability is unlikely to occur with conventional E-glass and is a problem specific to low-dielectric glass cloth.

[0091] On the other hand, it was found that the glass cloths of Comparative Examples 1 and 3 had low whiteness and poor insulation reliability. This was presumably due to the generation of flame-retardant viscous matter.

[0092] Also, in Comparative Examples 2 and 4, it is seen that although the whiteness degree gradually improves by doubling the heat cleaning treatment time, the degree of improvement cannot be said to be large.

[0093] Furthermore, in Comparative Example 5, although an attempt was made to wash off the sizing agent and the like before the heat cleaning treatment, no significant difference was observed compared to Comparative Example 3. In Comparative Example 6, it is found that the insulation reliability is poor for the glass cloth, which has a high weight loss coefficient and is prone to desorbing volatile components. [Industrial Applicability]

[0094] INDUSTRIAL APPLICABILITY The present invention has industrial applicability as a low dielectric glass cloth used for prepregs and the like.

Claims

1. A glass cloth constructed by using glass yarns made of a plurality of glass filaments as warp yarns and weft yarns, In the following formula (1), a weight reduction coefficient calculated as the product of the weight reduction rate derived from the glass component in a heat treatment at 380° C. for 2 hours and the average radius of the glass monofilament is 0.38 or more and 0.9 or less, Weight reduction coefficient=weight reduction ratio (%)×average radius of the glass filaments (μm) (1) The whiteness is 95 or more. Glass cloth.

2. The glass cloth, The Si content is SiO 2 In terms of mass conversion, it is 40 to 60 mass%, B content is B 2 O 3 In terms of mass conversion, it is 15 to 30 mass %, The glass cloth according to claim 1.

3. The Fe content is Fe 2 O 2 In terms of weight percent, it is 0.001 to 0.10% by weight. The glass cloth according to claim 1 or 2.

4. having a dielectric constant of 5.0 or less at a frequency of 1 GHz; The glass cloth according to any one of claims 1 to 3.

5. The glass cloth according to any one of claims 1 to 4, and a matrix resin impregnated in the glass cloth. Prepreg.

6. The glass cloth according to any one of claims 1 to 4 is provided. Printed wiring board.

Citation Information

Patent Citations

  • Method for heat cleaning glass fiber woven fabric

    JP2007262632A